A Major and Stable Quantitative Trait Locus qSS2 for Seed Size and Shape Traits in a Soybean RIL Population - Kumawat, Giriraj; Xu, Donghe (Frontiers in Genetics, 2021)
Seed size and shape traits are important traits determinants ofing seed yield and appearance quality in soybean (Glycine max (L.) Merr.). Identification TheUnderstanding the of genetic architecture dissectionarchitecture of seed size and shapethese traits is important for theirto enable their genetic improvement through efficient and targeted selection in soybean breeding, and for the identification of underlying causal genes. To map seed size traits (seed length, seed thickness, seed width, single seed weight,) and seed shape traits (ratios of length-to-width, length-to-thickness and width-to-thickness) in soybean, a recombinant inbred lines (RILs) population developed from K099 (small seed size) × Fendou 16 (large seed size), was phenotyped for in three growing seasons. A genetic map of the RIL population was developed using 1485 GRAS-Di and 177 SSR markers. Quantitative trait locius (QTLs) analysis mapping was conducted by inclusive composite interval mapping. using 229 SSRs genetic map of RILs have identified 33 As a result, 53 significant QTLs for seven seed size traits and 27 significant QTLs for seed shape traits were identified., among them, 18 are new to report. Seven Six of these stable QTLs (qSL2.2, qSW198.1, qSW16.1, qSLW2.1, qSLT2.1, qSWT1.12, and qSWT4.31 and qSWT18.1) were were identified, which were detected for two or more year’s phenotyping data with LOD scores of 3.80 -14.0 values and R2 of 2.36 % - 39.49% in at least two growing seasons.PVE (%) falling in the range of 3.21 - 11.09 and 7.82 - 37.05, respectively. Among the seven stable QTLs identified, four (qSL2.2, qSWT1.1, qSWT4.1 and qSWT18.1) are new to report. Among the above significant QTLs, 24 QTLs were grouped into 11 QTL clusters, such as, three stable three major QTLs (qSL2.23, qSLW2.1, and qSLT2.1) were co-localized clustered into in a major QTL the same genomic region of on GmChr.02, named as 'qSS2'. The effect of QTL hotspot 'qSS2' was validated in a pair of near isogenic lines, and its candidate genes (Glyma.02G269400, Glyma.02G272100, Glyma.02G274900, Glyma.02G277200 and Glyma.02G277600) were mined. The results of this study will assist in the breeding programs aiming at improvement of seed size and shape traits in soybean.